Understanding and Managing Public Organizations: Essential Texts for Nonprofit and Public Leadership and Management - Rainey, Hal G.; Fernandez, Sergio; Malatesta, Deanna; Fernandez, Sergio; Malatesta, Deanna (San Francisco: Wiley, 2021)
"Understanding and Managing Public Organizations, through five editions, has met a need in course curricula in graduate courses in public administration and affairs, and has served as a reference book for scholars and doctoral students in this field. The book presents the major ideas and insights from organization theory, which focuses on the main dimensions and processes of organizations, including organizational goals and effectiveness, strategy, decision-making, structure and design, organizational change, operating environments, and related topics. The sixth edition will be updated to reflect recent developments in the field since publication of the fifth edition in 2014."--
Keywords: Public administration